Improving Customer Satisfaction at Purwanegara Gas Station in Purwokerto Through Service Quality - Larasati Varahel Sumarnis; Arinastuti Arinastuti; Akbar Pahlevi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Objectives of the research this that is for knowing and analyzing: influence tangible, reliability, responsiveness, assurance, and empathy to customers satisfaction of Pertamina 44,531,33 Purwanegara gas station in Purwokerto. Type of research this is study survey with use approach quantitative. The sampling method used that is non-probability sampling and using technique accidental sampling. Amount samples obtained​ according to formula Cochran of 100 respondents. The data analysis technique used multiple linear regression with IBM Statistics SPSS 25 assistance. Results of the study this show that: tangible has an influence positive and significant to customers satisfaction, reliability influence positive and significant to customers satisfaction, responsiveness not influence positive to customers satisfaction, assurance influence positive and significant to customers satisfaction, empathy influence positive and significant to customers satisfaction. The results explain that hypothesis first, second, fourth and fifth accepted, hypothesis third rejected.